Participatory Research as the Technology for Social Innovation - Poviliūnas, Arūnas (Sociologija. Mintis ir veiksmas, 2003)
The article analyzes the arguments for the placing of participatory research in the practice of sociology. The changing societal conditions have forced social scientists, of which sociologists are a prime example, to alter the way sociology has been conceptualized and has been practiced in relation to social change. As practitioners of participatory research are maintaining traditional sociology is producing narratives and practices that are not in the interest of the excluded and marginalized people. In order to live up to the potential of sociology as a technology for the social innovation and social inclusion, it must include the interest and the wisdom of the people in its researching and theorizing activities. Participatory research provides an opportunity to realize this possibility.
Keywords: participatory research; social innovation; rural community; social exclusion